Image of the Other in the Novel Fathers and Forefathers by Slobodan Selenić - Bandic, Jovana N. (Collection of Papers of the Faculty of Philosophy in Priština, 2017)
The subject of interest of this paper is the imagological view of the novel Fathers and Forefathers by Slobodan Selenić. The story is based on the crossing of the two cultures (the Balkan and the Anglo-Saxon), whose insurmountable differences bring drama into family relationships. As typical examples of their ethnos, Elizabeth and Stevan Medaković, create images of themselves and of the Others. As they are not ready to overcome certain stereotypes based on ethnos, and as the fear of losing the national identity is even stronger than love, they fail to adapt and to fully embrace the Otherness. Due to his need to overcome the differences between himself and the surroundings, Mihajlo, the youngest member of the Medaković family, becomes the Other as opposed to his family and consciously goes into death, just to prove his nationality, that he is the same as they are.